Peningkatan Mutu Kurikulum SDTQ-T Irsyadul Aulad Banjarmasin - Rida (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This research aimed to explore more about the Quality Improvement of Elementary Schools SDTQ-T Irsyadul Aulad Banjarmasin. This research is conducted with descriptive qualitative as research method. The data were collected through with interviews with principal and teachers at SDTQ-T Irsyadul Aulad Banjarmasin about curriculum quality improvement. The results showed that curriculum implementation process at SDTQ-T Irsyadul Aulad Banjarmasin is carried out in accordance with the curriculum planning process that has been made and determined, then the curriculum is developed according to student needs and school characteristics. Although sometimes the lesson plans that have been made are not maximized during the learning process in the classroom. This will be a separate evaluation process for teachers to continue to improve the quality of their teaching in the classroom. Furthermore, indicators of curriculum development competence have been realized by teachers at SDTQ-T Irsyadul Aulad Banjarmasin concretely. But it's just not too optimal.